Abraham Flexner: the life trajectory of an educator - Hugo Spinelli (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2022)
This article centers on the life of Abraham Flexner, widely known in the field of health for the Flexner Report published in 1910, which is considered one of the most important theoretical discussions in the history of medical education. Flexner was first and foremost an educator, belonging to the progressive education movement led by John Dewey in the United States. The text analyzes the historical moment in which the health field began to consolidate in the United States, as well as the actors involved, the interests at play, the construction of doxa, and the role of philanthropic organizations and the American Medical Association. Flexner's critiques in the field of education were primarily focused on pedagogical approaches at different stages of education; he was particularly critical of the university level, postgraduate programs, and the absence of humanistic training, which had been supplanted by research. The article closes by raising the question of whether or not the problems related to education - and medical education in particular - identified by Flexner between the late 19th and early 20th century are still relevant to medical schools and universities in Latin American countries today.